#### Answer

$\dfrac{6a^{2}b-9ab}{3ab}=2a-3$

#### Work Step by Step

$\dfrac{6a^{2}b-9ab}{3ab}$
Take out common factor $3ab$ from the numerator and simplify:
$\dfrac{6a^{2}b-9ab}{3ab}=\dfrac{3ab(2a-3)}{3ab}=2a-3$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\dfrac{6a^{2}b-9ab}{3ab}=2a-3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.